The ‘Discovery of Writing’ in The Qur’an: Tracing An Epistemic Revolution in Late Antiquity - Angelika Neuwirth (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2016)
The present article is to take the Qur’an seriously as a literary text, the first literary text in Arabic language to be almost immediately put to writing and thus to become the trigger of the Islamic “culture of the Book” that soon after was to emerge. To enter the discourse of the Qur’an as a literary text demands first of all to tackle the essential question what the Qur’an is in terms of genre: a compilation of diverse previously circulating traditions, or the transcript of a historically real drama of the emergence of a community. This paper wishes to enter the discussion from another angle, looking at the Qur’an from a perspective which makes it possible to focus its epistemic potential, the dynamics that eventually triggered a fundamental renewal of the Late Antique world. This is a cultural turn which was achieved through the Qur’anic negotiation and re-interpretation not only of the neighboring monotheist traditions but no less of the ancient Arabic lexicon of concepts.